Extending rights' reach : constitutions, private law, and judicial power - Mathews, Jud (New York, NY : Oxford University Press, 2018)
Constitutional rights protect individuals against government overreaching, but that is not all they do. In different ways and to different degrees, constitutional rights also regulate legal relations among private parties in most legal systems. In other words, rights can have not only a vertical effect, within the hierarchical relationship between citizen and state, but also a horizontal one, on the citizen-to-citizen relationships otherwise governed by private law. In every constitutional system with judicially enforceable constitutional rights, courts must make choices about whether, when, and how to give those rights horizontal effect. This text is about how different courts make those choices, and about the consequences that they have.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 5, 2018).
Keywords: Civil rights -- United States; Civil rights -- Germany; Civil rights -- Canada; Civil law -- United States; Civil law -- Germany; Civil law -- Canada; Political questions and judicial power -- United States; Political questions and judicial power -- Germany; Political questions and judicial power -- Canada; Law; Laws of specific jurisdictions & specific areas of law